(untitled) (Research, Society and Development, 2021)
Lettuce is the main leafy species consumed in Brazil. Among other vegetables, it accumulates considerable levels of nitrate in its tissues, which may vary depending on the variety, cultivation system, geographic location, among others. Food security aims to monitor the level of substances harmful to human and animal health. The objective of this work was to evaluate the nitrate content in lettuce leaves of two varieties and in three production systems: conventional, organic and hydroponic. The fresh weight, dry weight and nitrate levels were determined in the Crespa and Mimosa varieties in all production systems in the Campo Grande-MS. The observed results showed significant variations in the levels of nitrate according to the cultivation systems and varieties. The organic system obtained the lowest levels of nitrate while the hydroponic system accumulated the most nitrate in the leaves. However, the nitrate levels observed in all evaluated production systems were lower than the maximum limits established by FAO / OMS and the European Union for both varieties.